Read in the special provisions for the responsibility of fire in the light of Law 19-02 on the general rules for the prevention of fire hazards and panic - Hazem, Fatiha (Journal of Human Sciences, 2020)
The legal protection of persons, property and the environment against fire hazards has always been limited to the right to compensation, based on the provisions of civil liability and penal sanctions, which are determined by the Penal Code. Therefore ,the study seeks to clrify the new provisions of Law 19-02 in its review. Focusing on the conditions of verification of fire responsibility, as well as the adoption of a set of preventive measures and the establishment of oversight committees to prevent the risks of fire and panic, while reinforcing punitive penalties against those responsible for the damage caused by the fire.